2018
DOI: 10.1371/journal.pone.0204752
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of frequency and contents of antenatal care visits in Bangladesh: Assessing the extent of compliance with the WHO recommendations

Abstract: BackgroundIn addition to the number of antenatal care (ANC) visits, the items of ANC services covered by ANC visits greatly influence the effectiveness of the ANC services. Recently the World Health Organization (WHO) recommended not only to achieve a minimum of eight ANC visits, but also to use a core set of items of ANC services for safe motherhood. This study examined the levels and determinants of frequency and contents of ANC visits in Bangladesh and thus assessed the level of compliance with the WHO reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
200
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(268 citation statements)
references
References 43 publications
60
200
5
3
Order By: Relevance
“…The number of ANC visits (a non-negative integer) is the target response variable for which this study aims to identify a proper count regression model. A number of explanatory variables at individual (woman), household, community, and regional levels have been considered based on recent studies on ANC utilization [6,9,13]. The bivariate relationship of the explanatory variables with the number of ANC visits were examined first by a developing simple PR model for each of the explanatory variables.…”
Section: Data Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of ANC visits (a non-negative integer) is the target response variable for which this study aims to identify a proper count regression model. A number of explanatory variables at individual (woman), household, community, and regional levels have been considered based on recent studies on ANC utilization [6,9,13]. The bivariate relationship of the explanatory variables with the number of ANC visits were examined first by a developing simple PR model for each of the explanatory variables.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Many studies have assessed the determinants of prenatal care attendance in Bangladesh, particularly focussing on the WHO guideline of taking at least four ANC visits [6][7][8][9], but only a few studies have assessed the determinants of the number of ANC visits in general [10][11][12][13]. It has been shown that there may be two separate processes that generate decisions regarding the use and frequency of prenatal care use [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most other studies measuring the quality of ANC through scores also gave arbitrary weights for each item, and most often the same weight for each intervention included. [29][30][31][32] Others relied upon data driven approaches such as principal components analyses, 17,33 but this ignores any theory in terms of the weights assigned. We started with a theoretical construct, and then showed that it was consistent with principal components results.…”
Section: Discussionmentioning
confidence: 99%
“…The Basic Antenatal Care (ANC) has emphasis on number of visits and hence not so popular with only an average 50% of mothers attend. [1][2][3][4][5] Over the years there have been so much socio cultural changes in the society and health care delivery system. Now we have adopted fully institutional deliveries by specialist birth attendants supported by free national ambulance service.…”
Section: Introductionmentioning
confidence: 99%